Metabolisme Energi Pakan pada Sapi Peranakan Ongole dan Sapi Peranakan Ongole x Limousin Jantan yang Mendapat Pakan Jerami Padi Fermentasi dan Konsentrat - Agung Purnomoadi; Nurhidayat Nurhidayat; Edy Rianto (Universitas Sebelas Maret (UNS), 2008)
An experiment was carried out to study energy metabolisability in Limousin Grade and Ongole Grade bulls fed fermented rice straw. This experiment used 4 Ongole Grade (OG) and 4 Ongole Grade x Limousin (OGL) bulls, aged 9 mths. Ongole Grade bulls weighed 109 ± 16 kg, while OGL bulls weighed 133 ± 25 kg. The feeds given were fermented rice straw (offered ad libitum) and concentrate (fed at 2.1% live weight). The breeds of cattle were compared to each other in an “Independent Sample Comparison” method. Parameters observed were energy intake, energy excretion through faeces, urine and methane, and live weight gain. The results showed that there was no significant difference (P>0.05) between OG and OGL in energy intake (58.2 MJ/d vs 74 MJ/d), nor in energy metabolisability (38,4% vs 43,4%) The LWG of OG (0,24 kg/d) was significantly (P<0.5) lower than that of OGL (0,47 kg/d). It was concluded that being given fermented rice straw, OG and OGL bulls had similar ability in dietary energy metabolism. Key Words: bull, breed, energy metabolism